2016
DOI: 10.1093/mnras/stv2841
|View full text |Cite
|
Sign up to set email alerts
|

The physical nature of the most metal-poor damped Lyman α systems

Abstract: Utilizing the high-resolution, large-scale LAOZI cosmological simulations we investigate the nature of the metal-poor ([Z/H] < −2) damped Lyman alpha systems (mpDLA) at z = 3. The following physical picture of mpDLAs emerges. The majority of mpDLAs inhabit regions 20 kpc from the host galaxy center on infalling cold gas streams originating from the intergalactic medium, with infall velocity of ∼ 100 km/s and temperature of ∼ 10 4 K. For each host galaxy, on average, about 1% of the area within a radius 150 kpc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…of the low-redshift DLAs were believed to be associated with extended disks, the inner circumgalactic medium, or satellite galaxies (e.g. Neeleman et al 2017), while simulations showed that the high-z DLAs were not necessarily galaxy disks (Gardner et al 2001;Pontzen et al 2008;Yajima et al 2012;Cen 2012;Rahmati et al 2013;Yuan & Cen 2016).…”
Section: Introductionmentioning
confidence: 99%
“…of the low-redshift DLAs were believed to be associated with extended disks, the inner circumgalactic medium, or satellite galaxies (e.g. Neeleman et al 2017), while simulations showed that the high-z DLAs were not necessarily galaxy disks (Gardner et al 2001;Pontzen et al 2008;Yajima et al 2012;Cen 2012;Rahmati et al 2013;Yuan & Cen 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The most metal-poor DLAs are thought to be the antecedents of the lowest mass galaxies (Salvadori & Ferrara 2012;Cooke, Pettini & Jorgenson 2015), as well as cold gas streams being accreted on to galaxies (Yuan & Cen 2016). Such an affiliation marks these DLAs as a promising environment to measure -at high redshift -the chemical abundance pattern of the earliest generation of stars.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true where the hot quasi-static halo interacts with cold rapidly-inflowing IGM accretion. Some of the resulting complications are revealed in the study of metal-poor DLAs carried out by Yuan & Cen (2016). The majority of the metal-poor DLAs are far from the central galaxy (≥ 20 kpc) and result from the cold gas streams from the IGM.…”
Section: Obvious Complications and Future Trendsmentioning
confidence: 99%